Українська хатня ікона XVIII – ХХ ст.: як наукове дослідження - Осадча, О. (Інститут народознавства НАН України, 2007)
The article is devoted to consideration of Ukrainian hut home icons as phenomena of scientific and cultural problem that needs of immediate sollution.